Optimizing Village Administration and Public Information Access through the Implementation of an Electronic Archive System in Desa Marga Mukti - Arifin, Ahmad (JLASA (Journal of Law and State Administration), 2025)
The development of digital technology has transformed administrative processes by providing faster, more efficient, and accessible solutions. In village governance, managing official correspondence remains a critical activity that often faces challenges in organization, accessibility, and transparency. This study presents the design and implementation of an electronic archive (e-archive) system for Desa Marga Mukti, Penarik District, Mukomuko Regency, using a mobile web-based platform. The system was developed with the Waterfall method, ensuring a structured and sequential approach to software development. The e-archive facilitates the management of incoming and outgoing correspondence, improves administrative efficiency, and supports public information disclosure. The system is user-friendly, easily accessible to village officials, and contributes to better governance by streamlining administrative tasks and promoting transparency in Desa Marga Mukti